2019
DOI: 10.31557/apjcp.2019.20.12.3735
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of c-Myc Immunohistochemical Expression in Muscle Invasive Urothelial Carcinoma of the Urinary Bladder: A Retrospective Study

Abstract: Objective: This study aimed to investigate the immunohistochemical expression of c-Myc in muscle invasive urothelial carcinoma (MIUC) of the urinary bladder and to evaluate the correlation of c-Myc expression with different clinicopathological parameters and outcome, including a relatively new histopathological tumor characteristic that is the growth pattern of tumor invasion. Methods: A total of 66 formalin-fixed and paraffin-embedded sections of MIUC obtained from radical cystectomy specimens were enrolled. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…28 Given the lack of prognostic impact of grade in muscle‐invasive urothelial carcinoma, it was recommended to avoid grading in these tumours in the WHO classification of genitourinary carcinomas since 2004. 29 Considering that molecular features with an unequivocal functional role in cancer cells such as p53 alterations, 30 HER2 overexpression, 31 and MYC 32 have also failed to be prognostic in most studies on pT2–4 bladder cancer demonstrates that the absence of a prognostic relevance of the expression of a specific gene in urothelial cancer does rule out a relevant role in tumour biology.…”
Section: Discussionmentioning
confidence: 99%
“…28 Given the lack of prognostic impact of grade in muscle‐invasive urothelial carcinoma, it was recommended to avoid grading in these tumours in the WHO classification of genitourinary carcinomas since 2004. 29 Considering that molecular features with an unequivocal functional role in cancer cells such as p53 alterations, 30 HER2 overexpression, 31 and MYC 32 have also failed to be prognostic in most studies on pT2–4 bladder cancer demonstrates that the absence of a prognostic relevance of the expression of a specific gene in urothelial cancer does rule out a relevant role in tumour biology.…”
Section: Discussionmentioning
confidence: 99%
“…However, Mohammed et al, (2019) showed that, c-Myc and BCL2 IHCs protein over expressions were comparable with RT-PCR c-Myc and BCL2 genes arrangements in understanding the DLBCL prognostication. Another study on c-Myc protein expression in bladder carcinoma showed it could predict the clinical behaviour of the disease (Elwy et al, 2019). IHC of c-Myc are now emerging as a favourable alternative as it is a cheaper and easier technique which can be used to study the effects of this protein in disease behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Histoscore (H-score) system was applied to quantify c-Myc expression with a range of 0-300. H-score was achieved by semi-quantitative assessment of both the intensity, classified as negative (0), weak (1+), moderate (2+) and strong (3+) and the percentage of positive cells according to the following formula (Elwy et al, 2019).…”
Section: Evaluation Of C-myc Immunostainingmentioning
confidence: 99%